Pengaruh 'Urf dalam Perubuhan Hukum Menerut Imam Ibn 'Abidin - Ahmad Zuhairuz Zaman (Mabahits : Jurnal Hukum Keluarga Islam, 2020)
This study examines the thought of Ibn ‘A<bidi>n in the discourse of the theory of Islamic law (usūl fiqh), particularly on the concept of‘ urf proposition and its implementation in Ibn ‘Ābidīn's fatwas. This study is focused on answering three important things: 1) how the concept of ‘urf proposition according to Ibn ‘Ābidīn; 2) how the variety of ‘urf and its division according to the view Ibn ‘Ābidīn; 3) how Ibn ‘Ābidīn applied the ‘urf proposition in some of his fatwas. The results of the study show that the concept of Ibn ‘A<bidi>n's urf theorem, both in terms of definition, the proposition of the hujjah's, the requirements, and the variety of divisions, is essentially nothing new in the activities of the law istinbat. He only tried to maximize the concept of ‘urf and related it in the formation of fiqh law that has been expressed by the previous fuqaha>’ and usu>liyyi>n. However, Ibn ‘A<bidi>n did not only present the concept of ‘urf proposition specificly to absolute mujtahids, but also presented it in the concept of‘ urf which can also be used by mufti and judges who have not reached the level of absolute ijtiha>d. Ibn ‘A<bidi>n divided the‘ urf in four points of view. First, the division of ‘urf in terms of its laying resources. Second, the division of ‘urf in terms of its form. Third, the division of ‘urf in terms of its validity. Fourth, the division of ‘urf in terms of contradictions with other propositions, either in the form of shar‘i or za>hir's narration of al-madhhab. The first three divisions have been widely reviewed by previous fiqh experts. The final division, in the author's view, is not found from the jurists before Ibn ‘A<bidi>n who examines specifically the division of url contradictions with other such propositions. That is Allah a‘lam. According to Ibn ‘A<bidi>n, when in a situation contradictory to other propositions, ‘urf is sometimes a general ‘urf and special ‘urf. As for general ‘urf, if its use is precisely the consequence of leaving nass shar‘i>, then its status is not considered. However, the general ‘urf is acceptable if the contradiction with nass shar‘i> on some sides only, so it can be a mukhassis that takhsi>s nass shar‘i>'s announcement. While the special ‘urf can be acknowledged if there is no contradiction with the nass shar‘i> at all, the disagreements are evenly distributed on all sides as well as on some sides only. Strictly speaking, the special ‘urf can not be a mukhassis that takhsi>s the nass shar‘i>'s announcement. Then if the general ‘urf and special ‘urf conflict with za>hir al-madhhab history, then both can be accepted as a proposition, only in the application of the law based on ‘urf, only specifically applicable locally to the region or place of the perpetrators only, universally applicable. The application of the theory of ‘urf, besides it is as the representation of taqli>d in manhaji> (methodology); it is also one form of activities of istinba>t in using ijtiha>d intiqa’i> and ijtiha>d insha>’i>. The intiqa’i> method refers to the classical ulama> fatwas relevant to the development of the times. While insha>’i> is the method of ijtiha>d over new problems that are not in the nass directly or in the ulama> classical fatwa. The method of ijtiha>d intiqa’i> applied by Ibn ‘A<bidi>n can be seen in his fatwa on the possible sale and purchase of fruit still in the tree. He took and searched the opinion of Abu Bakr Muhammad bin al-Fadl and al-Halwa>ni who allowed the sale. The example of ijtiha>d insha>’i> is applied by Ibn ‘A<bidi>n in his fatwa concerning the prohibition of the practice of the su>karah contract if it is held in the jurisdiction of Islam, and can become lawful if the contract is held in the jurisdiction of the harb state. The practice of su>karah in today is popular with the term of expedition insurance. Even the fatwa contained in the book of Ha>shiyah Radd al-Mukhta>r is the only discussion of insurance coverage that can be found in the treasures of tura>th al-madhhab, although some contemporary fuqaha> disagree with Ibn‘A<bidi>n application on the practice of modern insurance.",